Fast Leaps between Millisecond Confinements Govern Ase1 Diffusion along Microtubules. Issue 10 (16th August 2021) - Bujak, Łukasz; Holanová, Kristýna; García Marín, Antonio; Henrichs, Verena; Barvík, Ivan; Braun, Marcus; Lánský, Zdeněk; Piliarik, Marek
Abstract: Diffusion is the most fundamental mode of protein translocation within cells. Confined diffusion of proteins along the electrostatic potential constituted by the surface of microtubules, although modeled meticulously in molecular dynamics simulations, has not been experimentally observed in real‐time. Here, interferometric scattering microscopy is used to directly visualize the movement of the microtubule‐associated protein Ase1 along the microtubule surface at nanometer and microsecond resolution. Millisecond confinements of Ase1 and fast leaps between these positions of dwelling preferentially occurring along the microtubule protofilaments are resolved, revealing Ase1's mode of diffusive translocation along the microtubule's periodic surface. The derived interaction potential closely matches the tubulin‐dimer periodicity and the distribution of the electrostatic potential on the microtubule lattice. It is anticipated that mapping the interaction landscapes for different proteins on microtubules, finding plausible energetic barriers of different positioning and heights, can provide valuable insights into regulating the dynamics of essential cytoskeletal processes, such as intracellular cargo trafficking, cell division, and morphogenesis, all of which rely on diffusive translocation of proteins along microtubules. Abstract : Interaction mechanisms involved in the diffusive motion of single proteins on microtubules are revealed by direct optical tracking at a very high spatiotemporal resolution. The diffusive motion is characterized by rapid stepping between confinements associated with tubulin dimers allowing to reconstruct the energy landscape of the interaction experimentally in a close match with theoretical predictions.